Optimal Candidates to Do Fresh Embryo Transfer in Those Using Oral Contraceptive Pretreatment in IVF Cycles - Lu, Yao; Niu, Yichao; Wang, Yuan; He, Yaqiong; Ding, Ying; Lu, Xinyuan; Xu, Bing; Lindheim, Steven R.; Sun, Yun (Frontiers in Physiology, 2021)
Objective: Concern regarding the adverse impact of pretreatment of oral contraceptives (OC) prior to ovarian stimulation for in vitro fertilization (IVF) on pregnancy outcome has been debated. We investigated factors that may be associated with live birth rate (LBR) in fresh embryo transfer cycles after OC pretreatment. Methods: A retrospective study was conducted at the Reproductive Center of Ren Ji Hospital, Shanghai, China. 814 women aged 20–35 years undergoing their first autologous IVF cycle and fresh embryo transfer after OC pretreatment were included. Long gonadotropin releasing hormone (GnRH) agonist (a) or GnRH antagonist (ant) protocol was used for ovarian stimulation. Predictive factors for LBR were identified using multivariate logistic regression analysis. Results: Multivariate logistic regression analysis demonstrated that using GnRH-ant protocol for ovarian stimulation was associated with significantly lower LBR (OR 0.70, 95% CI 0.52-0.93), while endometrial thickness on day of hCG trigger was associated with increased LBR (OR 1.16, 95% CI 1.06-1.27). Despite comparable patients’ age, duration of infertility, BMI and basal FSH between GnRH-a and GnRH-ant groups, those using GnRH-ant resulted in significantly lower LBR compared to the GnRH-a group (37.4% vs. 48.5%, p=0.002). Using ROC analysis and a cut-off endometrial thickness < and ≥9.5mm, those <9.5mm using GnRH-ant resulted in significantly lower LBR (28.5% vs. 43.4%, p=0.004), while no differences were noted with an endometrial thickness ≥9.5mm (49.6% vs. 51.1%, p=0.78). Conclusions: Live birth was significantly impacted in OC pre-treated GnRH-ant cycles with an endometrial thickness <9.5mm on day of hCG trigger. Cryopreservation of all embryos in these cycles should be considered.